2019
DOI: 10.5847/wjem.j.1920-8642.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical dehydration using point of care ultrasound for pediatric patients in rural Panama

Abstract: BACKGROUND: Dehydration and its associated symptoms are among the most common chief complaints of children in rural Panama. Previous studies have shown that intravascular volume correlates to the ratio of the diameters of the inferior vena cava (IVC) to the aorta (Ao). Our study aims to determine if medical students can detect pediatric dehydration using ultrasound on patients in rural Panama.METHODS: This was a prospective, observational study conducted in the Bocas del Toro region of rural Panama. Children b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…[18][19][20] However, these results have been refuted in further studies. 21,22 Urine testing has also been considered as a marker of dehydration, although a prospective cohort study found urinary specific gravity and urine ketones did not correlate with degree of pediatric dehydration. 23 A meta-analysis of noninvasive methods for diagnosis of pediatric dehydration also found that available did not support ultrasound or urinalysis for routine assessment of pediatric dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] However, these results have been refuted in further studies. 21,22 Urine testing has also been considered as a marker of dehydration, although a prospective cohort study found urinary specific gravity and urine ketones did not correlate with degree of pediatric dehydration. 23 A meta-analysis of noninvasive methods for diagnosis of pediatric dehydration also found that available did not support ultrasound or urinalysis for routine assessment of pediatric dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Several initial studies showed promising results 18–20 . However, these results have been refuted in further studies 21,22 . Urine testing has also been considered as a marker of dehydration, although a prospective cohort study found urinary specific gravity and urine ketones did not correlate with degree of pediatric dehydration 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results differ from those of previous studies in North American children showing that an IVC/Ao ratio ≤ 0.8 modestly predicts severe dehydration after acute diarrhoea [ 24 , 35 ]. However, using the same cutoff value among rural children in Panama, Mazza et al found no difference in IVC/Ao ratio between children with and without severe dehydration [ 49 ]. Two additional paediatric studies, one conducted in Rwanda [ 50 ], the other in Bangladesh [ 51 ], found a significant correlation between the aorta-to-IVC ratio and dehydration in children with acute diarrhoea; the larger study from Bangladesh concluded, however, that a cutoff value ≥ 2.0 was not sufficiently accurate to recommend as a stand-alone screening tool for dehydration in children [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Median (IQR) IVC-CI on enrolment was increased in malaria patients (42% [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]) relative to healthy participants (35% [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]; p = 0.01), but was similar between patients with severe (38% ) and uncomplicated malaria (44% [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]; p = 0.055). The share of p...…”
Section: Markers Of Clinical Severitymentioning
confidence: 99%
“…Several studies have demonstrated the feasibility of medical students using POCUS and have included teaching multiple POCUS applications to medical students simultaneously [2,4,5]. However, there are few studies demonstrating medical students' ability to accurately perform POCUS on pediatric patients and these studies have typically included one POCUS application taught at a time [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%